El argumento de la locura - Porchat Pereira, Oswaldo (2005)
The argument explores the possible consequences of a philosopher´s critical revision of his own beliefs and certainties, in which he would consider the possibility of being mad. Although the argument is developed in the first person -with a Cartesian profile alien to the argumentative pattern of ancient Pyrrhonic scepticism- it nevertheless ends with a sceptical conclusion. It radically challenges and checkmates classical reason's ideals of certainty and absolute. Knowledge.